2016
DOI: 10.4103/2231-0762.186788
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality among dental students and its association with academic performance

Abstract: Objective:To investigate the sleep patterns of dental students from different academic levels and to determine the effect of sleep patterns on the academic performance of students.Methods:A self-reported questionnaire was designed and distributed among 1160 students from clinical and non-clinical levels to measure the sleep-related variables and academic performance. The questionnaire included questions on demographics, sleep habits, sleep quality index (PSQI), and grade point averages (GPAs). Data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 22 publications
2
33
4
Order By: Relevance
“…Gilbert et al in 2010 [ 21 ] found that the average number of sleep hours in a sample of 557 undergraduate Introductory Psychology students was 7.2±1.2, which is congruent with our research findings that the mean number of sleep hours at night for all students was 7.17±1.34 and the average PSQI score was 2.63±2.08. On the other hand, it is contrary to the study done by Elagra et al in 2016 [ 22 ] on dental students of Riyadh Colleges of Dentistry and Pharmacy, where the authors found the mean sleep duration to be less (5.85±1.853) and PSQI average score to be high (7.6±3.396). Though the mean sleep hours obtained from the current study is somewhat higher in comparison to other surveys, it is still less than the mean of 8 hours one would expect in a normal distribution of sleep duration.…”
Section: Discussioncontrasting
confidence: 72%
“…Gilbert et al in 2010 [ 21 ] found that the average number of sleep hours in a sample of 557 undergraduate Introductory Psychology students was 7.2±1.2, which is congruent with our research findings that the mean number of sleep hours at night for all students was 7.17±1.34 and the average PSQI score was 2.63±2.08. On the other hand, it is contrary to the study done by Elagra et al in 2016 [ 22 ] on dental students of Riyadh Colleges of Dentistry and Pharmacy, where the authors found the mean sleep duration to be less (5.85±1.853) and PSQI average score to be high (7.6±3.396). Though the mean sleep hours obtained from the current study is somewhat higher in comparison to other surveys, it is still less than the mean of 8 hours one would expect in a normal distribution of sleep duration.…”
Section: Discussioncontrasting
confidence: 72%
“…This was important because poor sleep patterns are linked to poor physical and mental health, 1,22 and poor academic performance. 13 Our study found that over two-thirds of freshman college students experienced PSQ. Although this rate was high, it was similar to that of Portuguese nursing students-reported by Silva et al, 23 Turkish medical students, 1 and Saudi medical and dental students.…”
Section: Discussionmentioning
confidence: 55%
“…Although this rate was high, it was similar to that of Portuguese nursing students-reported by Silva et al, 23 Turkish medical students, 1 and Saudi medical and dental students. 5,13 In these previous studies, PSQ among college students was linked to stress resulting from academic life. 13,24 However, PSQ was, consequently, linked to low GPA achievement and poor academic performance among medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that isolation and unhealthy behaviors due to changes in environment may explain these findings. [24][25][26] Since data on students' lifestyles and sense of isolation are not available, we have not assessed the effect of these possible medi-ators. Future studies may be warranted to investigate their effect.…”
Section: Discussionmentioning
confidence: 99%